Fracturing of Revision of a Cobalt-chrome Femoral Head after Fracturing of a Ceramic Femoral Head, with Diffuse Metallosis. Case Report() - Marques, Pedro Miguel Dantas Costa (Rev Bras Ortop, 2013)
We presente a case of a fracture of a cobalt-chrome femoral head after revision of a hip total prosthesis with ceramic femoral head fracture. During surgery we found the cobalt- chrome femoral head fracture, wear of the polyethylene and massive metallosis in muscular and cartilaginous tissue. Both femoral stem and acetabular cup were stable and without apparent wearing. After surgical debridement, we promoted the substitution of the femoral head and the acetabular polyethylene by similar ones. After 12 months of follow- up, the patient has no pain complaints, function limit or systemic signs associated with malign metallosis.